Enhancement of Spontaneous Fibrinolytic Activity in Diabetic Retinopathy - Ostermann, Helmut; Tschöpe, Diethelm; Greber, Wolfgang; Meyer-Rüsenberg, Hans-Werner; van de Loo, Jürgen (Thrombosis and Haemostasis, 1992)
The fibrinolytic system was studied in 96 patients with type I diabetes mellitus. Patients were grouped according to their degree of retinopathy; 38 patients with no evidence of retinopathy, 28 patients with background retinopathy and 30 patients with proliferative retinopathy. Thirty healthy individuals served as controls. The basal fibrinolytic activity as measured by clot lysis time and t-PA activity was increased in diabetic patients. This was associated with low levels of plasminogen activator inhibitor. Increased levels of D-dimer in diabetic patients further indicate enhanced in vivo fibrinolysis. The increase in fibrinolytic activity was highest in diabetics without retinopathy, and decreased with increasing retinopathy. Endothelial release of t-PA after venous occlusion was not different between controls and all diabetic groups. These findings suggest that in type I diabetics the fibrinolytic system is in an activated state. With worsening of retinopathy this increase in fibrinolytic activity diminishes.